(untitled) - Laura Lemay (Indiana, 1996)
Understanding HyperText and the world wide Web; Simple Web Documents; Doing more; HTML moves Ahead; Multimedia on the web: Images, Sound, and video; Designing Effective documents; Putting it all Online.
Keywords: computer programs - study and teaching,internet ( computer network ) - study and teaching